Literature Review: Effectiveness of Moringa Leaf Plants (Moringa oleifera) on Male Hormones - Niken Ayu Prachelia Putri; Elsa Yuniarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The herbal plant moringa leaves, or Moringa oleifera, have therapeutic properties. Several compounds, including vitamins, alkaloids, amines, lignin, flavonoids, quinones, coumarins, tannins, terpenoids, and betalain phenolic acids, can be extracted from moringa leaves. This study set out to review the literature in order to gather broad knowledge regarding the impact of moringa leaves on male hormones. The research method is a literature review, searching for relevant sources Google Scholar in the 2010-2022 period. Based on a literature review of various research results, it is proven that the compounds contained in Moringa leaves (Moringa Oleifera) have a significant effect on male hormones.